Improving the Quality of Courier Services during a Pandemic with Theory of Inventive Problem Solving (TRIZ) - Nabila Noor Qisthani; Achmad Zaki Yamani; Isnaini Nurisusilawati; Farid Nugroho (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2022)
The increase in transactions through e-commerce due to changes in consumer buying behavior during the COVID-19 pandemic affected the demand for logistics services for the delivery of goods. The quality of logistics services can affect customer satisfaction and loyalty, and logistics service companies must provide added value to the services provided. This is what underlies the making of this research to be able to provide innovation proposals and improve service quality to courier service providers to support government programs to improve the quality of national logistics services. The method used in this research is Logistic Service Quality (LSQ), which analyzes problems in courier services. Theory of Inventive Problem Solving (TRIZ) is used to solve problems in the object of research and provide suggestions for improvement.